Comparative study of naphthalocyanine-based near infrared organic photodiode using VTTBNc:PC61BM and VTTBNc:PC71BM blend films / Siti Anis Khairani Alwi - Siti Anis Khairani , Alwi (2022)
In this work, the experimental evaluation of solution-processed bulk heterojunction organic photodiodes using vanadyl 2,11,20,29-tetra-tert-butyl-2,3-naphthalocyanine (VTTBNc) as an electron donor has been presented. VTTBNc is blended with two different fullerene derivatives and served as electron acceptor in which influence the performance of organic photodiode (OPD). The fullerene derivatives involved are [6,6]phenyl-C61-butyric acid methyl ester (PC61BM) and [6,6]phenyl-C71-butyric acid methyl ester (PC71BM). Three different ratios (1:0.5, 1:1.0, 1:1.5) (vol:vol) of VTTBNc:PC61BM and VTTBNc:PC71BM blend films have been varied in the characterization and optimization of the OPD devices. The blended film of the ratio 1:1.5 and 1:1.0 were found to be the optimized based on the OPD performance for VTTBNc:PC61BM and VTTBNc:PC71BM, respectively. The blend film of VTTBNc:PC71BM (vol:vol 1:1.0) exhibits the highest performance in the VTTBNc blend structure with 2.31x109 Jones detectivity and 26.11 mA/W responsivity at -1 V bias. Besides that, the blend by using PC71BM shows the enhancement of the morphology as it exhibits higher visibility of the cluster on the surface with surface roughness increased to 62%. The light absorption measurement demonstrated that VTTBNc in the blend film can extend the absorption to the near-infrared (NIR) region furthering in more application for the photodiode. Moreover, the HOMO-LUMO levels of VTTBNc were found to be as -5.14 eV and -3.74 eV which properly aligned with the energy levels in fullerene derivatives.